Pengaruh Audit Fee dan Audit Tenure terhadap Kualitas Audit: Studi pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Devi Natalia Tlonaen; Herly M. Oematan; Junita Cestilia Nenabu (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of audit fee and audit tenure on audit quality in infrastructure companies. This research employs a quantitative method, with audit fee and audit tenure as independent variables, and audit quality as the dependent variable. Secondary data were obtained from the Indonesia Stock Exchange (IDX) for the period 2021–2023. The study used a sample of 36 observations selected through purposive sampling. The data analysis method used is multiple linear regression. The results show that audit fee has no significant effect on audit quality, meaning that the amount of compensation paid for audit services does not determine the level of audit quality produced. Audit tenure also has no significant effect on audit quality, indicating that the length of the relationship between the auditor and the client does not directly influence the quality of the audit. Therefore, both audit fee and audit tenure, whether partially or simultaneously, do not have a significant effect on audit quality.